Sustained exposure to systemic endotoxin triggers chemokine induction in the brain followed by a rapid influx of leukocytes - Carolyn A. Thomson; Alison McColl; Gerard J. Graham; Jonathan Cavanagh (Journal of Neuroinflammation, 2020)
Abstract Background Recent years have seen an explosion of research pertaining to biological psychiatry, yet despite subsequent advances in our understanding of neuroimmune communication pathways, how the brain senses and responds to peripheral inflammation remains poorly understood. A better understanding of these pathways may be important for generating novel therapeutics to treat many patients with chronic inflammatory diseases who also suffer from neuropsychiatric comorbidities. Here we have systematically assessed the leukocyte infiltrate to the brain following systemic endotoxin exposure to better understand this novel route of neuroimmune communication. Methods Mice were injected intraperitoneally with LPS daily for 2, 5 or 7 consecutive days. We systematically interrogated the subsequent induction of chemokine transcription in the brain using TaqMan low-density arrays. A combination of flow cytometry and immunohistochemistry was then used to characterise the accompanying leukocyte infiltrate. Results Repeated LPS challenges resulted in prolonged activation of brain-resident microglia, coupled with an increased local transcription of numerous chemokines. After 2 days of administering LPS, there was a marked increase in the expression of the neutrophil chemoattractants CXCL1 and CXCL2; the monocyte chemoattractants CCL2, CCL5, CCL7 and CCL8; and the lymphocyte chemoattractants CXCL9, CXCL10 and CXCL16. In a number of cases, this response was sustained for several days. Chemokine induction was associated with a transient recruitment of neutrophils and monocytes to the brain, coupled with a sustained accumulation of macrophages, CD8+ T cells, NK cells and NKT cells. Strikingly, neutrophils, monocytes and T cells appeared to extravasate from the vasculature and/or CSF to infiltrate the brain parenchyma. Conclusions Prolonged exposure to a peripheral inflammatory stimulus triggers the recruitment of myeloid cells and lymphocytes to the brain. By altering the inflammatory or metabolic milieu of the brain, this novel method of immune-to-brain communication may have profound implications for patients with chronic inflammatory diseases, potentially leading to neuropsychiatric comorbidities.